After the conservation of Rubus ulmifolius (Rosaceae) - Ferrer-Gallego, P. Pablo; Beek, Abraham Van De (Phytotaxa, 2024)
The consequences of the conservation of the name Rubus ulmifolius and related issues are discussed. Special attention is paid to R. creticus and the two names of R. inermis. A new status and name is given to R. inermis Pourret: R. ulmifolius f. sancti-francisci; and R. inermis Willdenow was provided with a new name: R. auritus; an epitype for this name is also designated.